Damage Control Resuscitation in Pediatric Trauma Patients - Noureen, Sadaf; Mahwish Noor Ul Haq; Sharif, Muhammad; Umm-E-Rubab; Javed, Muhammad Habib; Fatima , Nimra (Indus Journal of Bioscience Research, 2025)
Background: Pediatric Damage control resuscitation and massive blood transfusions are widely practiced globally, yet there is a lack of comprehensive data on pediatric massive transfusion protocols (MTPs) and their outcomes. We present a pediatric DCR and evaluate its effects on morbidity and mortality. Methods: Using a Randomized Control Trial, we gathered the data on all pediatric trauma patients who presented from January 2022 to September 2022 in emergency department of pediatric surgery, Mayo hospital, Lahore. Our study encompassed patients who received blood products according to the DCR protocol as well as patients who were transfused crystalloids and whole blood according to conventional protocol. Outcomes between groups were compared. Results: A total of 58 patients were included, with 29 patients in the DCR group and 29 patients receiving blood according to conventional protocol (control group). Mortality was significantly different between groups.( 6.89 % in DCR group versus 27.58 % in control group, p-value : 0.027) Injury Severity Score for the two groups was not statistically different.( 20 ± 11 in DCR group vs 20 ± 12) Incidence of thromboembolic complications was found to be equal in both groups.(3.44% in each group) Coagulopathy, indicated by partial thromboplastin time (PTT) greater than 36, was linked to crystalloids and whole blood use.( 3.44% in DCR group versus 20.69% in control group, p-value : 0.044). Conclusion: DCR have been widely implemented in hospitals to lessen coagulopathy associated with hemorrhage. Blood transfusion via DCR is associated with decreased mortality and decrease incidence of coagulopathy. These findings endorse the implementation of pediatric DCR and highlight the need for additional research to understand its key factors and effects.